Theoretical and Applied Principles of Strategic Management of Competitive Advantages of Enterprises in the Context of Digitalization - Zaverbnyj, A.; Pushak, Ya. (Економічний вісник Донбасу, 2023)
The article highlights the main theoretical and applied principles of strategic management of competitive advantages of enterprises in the context of digitalization. The paper analyzes the problems of strategic management of competitive advantages at the macro and micro levels. Since the management of domestic enterprises is simply forced to make decisions under conditions of critical uncertainty, in the absence of practical experience in wartime, the dynamic development of innovative technologies, and the digitalization of the economy, the study and improvement of the strategic management of competitive advantages of enterprises in the context of digitalization are topical issues. It has been established that the current highly dynamic pace of development of the economic environment will primarily be reflected in enterprises. Digitalization, active introduction, development of the latest technologies in the activities of these enterprises will also entail changes in approaches to ensuring the competitive position of the enterprise in the markets. It is determined that adaptation to changes in domestic enterprises should be ensured by internal changes in their systems of activity, reflected in their strategic development. It has been substantiated that the dynamics cause fierce competition and the need for enterprises to adapt to it. Domestic enterprises were unable to immediately respond to changing conditions, market needs, etc., which is why many of them were simply not ready for such competition. The paper determines that, in general, digitalization has a significant impact on the level of competitiveness. The key effects that can contribute to improving their level of efficiency and ensuring competitive advantage are allocated. The mechanism for implementing a strategy for achieving competitive advantages by domestic enterprises in the context of digitalization is a set of directions, measures, and tools aimed at achieving a competitive position of an enterprise in the market by introducing advanced technologies into business processes, which will allow achieving a cost leadership position, differentiating products and services in the market, or a strategy for entering foreign markets, etc. The structure of digital tools that can be used in practice in the formation and further development of competitive advantages of enterprises is proposed in the article.